Health consequences and aggravations evidenced by COVID-19 in Brazilian indigenous populations: an integrative review (Research, Society and Development, 2021)
This study aimed to carry out an integrative review of studies that identified the influence of the pandemic on the health of Brazilian indigenous peoples, in order to group this information and generate data relevant to a qualitative analysis. Searches were performed in the Scielo, Pubmed and BVS databases, using the descriptors “covid-19”, “indigenous” and “Brazil” connected by the Boolean operator “AND”. Only scientific articles published in the last 05 years, with free access, and whose content was written in Portuguese or English, were considered. In total, 22 articles were found, and 10 of them were considered in the composition of the results. It was observed that the main factors of the indigenous reality evidenced by the pandemic context are associated with the consequences arising from social isolation (failure in the supply of food, threats from land grabbers, and migration from urban centers to villages), geographic barriers (difficulty in medical care due to strict border surveillance), and cultural aspects (refusal in the use of synthetic medicines, performance of ritualistic group ceremonies, and confinement of many people in the same environment). Indigenous ethnic groups have faced several aggravations caused by the pandemic, which has served as obstacles to the implementation of health care that does justice to the specificities of this people, being necessary - in view of the challenges posed by the pandemic - to strengthen specific care sectors, in addition to ensuring the participation of indigenous leaders in the process of building healthy public policies.